(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Bilingualism and multilingualism have become increasingly relevant in today's globalized world. This article explores various theories surrounding bilingualism and multilingualism, including cognitive, sociolinguistic, and educational perspectives. It also discusses the implications for language learning, emphasizing the cognitive advantages, cultural enrichment, and practical applications in diverse settings.